Adherence to physical activity recommendations and physical and mental health risk in people with severe mental illness in Uganda. (February 2018) - Vancampfort, Davy; Probst, Michel; Basangwa, David; De Hert, Marc; Myin-Germeys, Inez; van Winkel, Ruud; Ward, Philip B.; Rosenbaum, Simon; Mugisha, James
Abstract: This study investigated cardio-metabolic risk factors among patients with severe mental illness who do or do not meet the recommendations of 150 min per week of physical activity. A secondary aim was to assess whether those that do meet the recommendations report lower levels of mental health symptoms. 107 (60♀) Ugandan in- and outpatients (mean age=34.4 ± 9.7 years) with severe mental illness (depression=7, bipolar disorder=55, schizophrenia=45) completed the Physical Activity Vital Sign (PAVS) method and Brief Symptoms Inventory −18. Participants were also screened for abdominal obesity (waist circumference>90 cm), overweight (body mass index≥25) and hypertension (systolic pressure≥140 mmHg and/or diastolic pressure≥90 mmHg).48.6% (n = 52) of patients met the physical activity recommendations as assessed by the PAVS method. 41.1% (n = 44) were overweight, 40.2% (n = 43) had abdominal obesity and 23.4% (n = 25) had hypertension. Those who did not meet the physical activity recommendations were significantly older, had a higher BSI-18 somatisation score, and had a higher risk of overweight [relative risk (RR) = 2.88, 95% confidence interval (CI) = 1.59–4.99], abdominal obesity (RR = 1.82, 95%CI = 1.13–2.93), and hypertension (RR = 2.16, 95%CI = 0.99–4.73). The PAVS is a feasible method of assessing physical activity among patients with severe mental illness in a low resource setting. The PAVS may have clinical utility for physical and mental health risk stratification. Highlights: The PAVS is a feasible method to identify patients with mental illness who do not comply with physical activity norms. The PAVS can quickly identify those who might be at risk for cardio-metabolic diseases. The PAVS may help promote the importance of physical activity prescription as a core part of the mental health treatment.